Prognostic value of systemic immune-inflammation index in patients with small-cell lung cancer treated with immune checkpoint inhibitors - Yusuke Hamakawa; Ayumi Hirahara; Akiko Hayashi; Kota Ito; Hiroyuki Shinohara; Aya Shiba; Yuko Higashi; Masaharu Aga; Kazuhito Miyazaki; Yuri Taniguchi; Yuki Misumi; Yoko Agemi; et al. (BMC Cancer)
Abstract Introduction The systemic immune-inflammation index (SII) has emerged as a promising prognostic marker in various malignancies. However, its prognostic significance in patients with small-cell lung cancer (SCLC) treated with immune checkpoint inhibitors (ICIs) remains unclear. In this study, we evaluated the prognostic impact of the SII in patients with SCLC after ICI use. Methods Of 62 patients with SCLC who received chemoimmunotherapy at our institution between September 2019 and July 2024, we retrospectively analyzed 36 patients who subsequently received ICI maintenance therapy following the initial chemoimmunotherapy treatment. The SII was calculated at the start of the second cycle of the ICI maintenance therapy. Patients were stratified into high (≥ 570) and low (< 570) SII groups. Overall survival (OS) and progression-free survival (PFS) were compared between the groups using the Kaplan–Meier method and log-rank test. Multivariate analysis using the Cox proportional hazards model was performed to identify independent prognostic factors. Results The high SII group exhibited a significantly shorter OS (median 12.1 vs. 24.1 months, P = 0.010) and PFS (median 5.2 vs. 8.1 months, P = 0.026) than those in the low SII group. A multivariate analysis identified SII ≥ 570 as an independent negative prognostic factor for OS (hazard ratio 3.83, 95% confidence interval 1.38–10.6, P = 0.010). Conclusions Elevated SII in the initial phase of ICI maintenance therapy was associated a with poor prognosis in patients with SCLC, supporting its utility as a prognostic biomarker in this setting. Therefore, prospective validation is required to confirm these findings.